Methodology for Analysis of Financial and Economic Security: Management of Capital Flows - Ye. Likhtenshteina, V.; P. Los’a, V.; V. Rossb, G.; D. Tyshuk, E. (International Journal of Engineering and Technology, 2018)
A methodology which is based on the theory of equilibrium random processes based on the evolutionary-simulation model and Decision instrumental system is proposed. The main stages of capital flow modeling are proposed. This is an analysis of the situation in which it can be interpreted. The structure of the flow of water and the market mechanism were determined. Themainstagesofcapitalflowmodelingareproposed.Â